2017
DOI: 10.2147/opth.s135068
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of in vivo performance of two point-of-care tear film osmometers

Abstract: PurposeTo compare the in vivo precision of two commercially available point-of-care osmometers among normal subjects with no dry eye disease.MethodsTwenty healthy adults with healthy ocular surfaces were evaluated by licensed eye care practitioners. All subjects had low Ocular Surface Disease Index score (<5), normal tear breakup time (>10 seconds), and no evidence of corneal fluorescein staining. Five consecutive measurements of tear osmolarity were measured on each eye using each of the two osmometers: the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 23 publications
2
39
2
Order By: Relevance
“…Tear film osmolarity was measured using a noninvasive, commercially available instrument (TearLab Ò , OcuSens Inc, San Diego, USA) at the indicated time points. Reproducibility of the instrument has been published previously [13,14].…”
Section: Tear Film Osmolaritymentioning
confidence: 99%
“…Tear film osmolarity was measured using a noninvasive, commercially available instrument (TearLab Ò , OcuSens Inc, San Diego, USA) at the indicated time points. Reproducibility of the instrument has been published previously [13,14].…”
Section: Tear Film Osmolaritymentioning
confidence: 99%
“…While repeated measurements over a period of time have been shown to be low and stable in normal subjects, DED subjects showed relatively elevated and unstable readings; indeed, the variability of osmolarity or increasing variation with increasing value is a statistical characteristic called heteroscedasticity and might be considered as a clinical indication of the loss of tear film homeostasis that occurs with dry eye . In this study, inter‐session reproducibility of Fiske 110 showed no differences between sessions or the correlation between the means and differences for both protocols.…”
Section: Discussionmentioning
confidence: 51%
“…Subjects were recruited among patients visiting the Optometry Clinic of the Optometry Faculty (Universidad de Santiago de Compostela) for an eye examination. As the aim of the study was to evaluate the inter‐session reproducibility of the protocol previously reported, only healthy volunteer subjects were recruited in order to avoid any interference of other possible variables in the analysis …”
Section: Methodsmentioning
confidence: 99%
“…Second, osmolarity measurements obtained using the I-PEN system may not be accurate, although Chan et al reported that the I-PEN system yielded rapid and accurate measurements of tear osmolarity in their “simulated testing setting” [ 23 ]. In contrast, some studies comparing different osmolarity measurement systems reported inferior repeatability of I-PEN measurements compared to those of other instruments [ 24 , 25 ]. It is possible that contact between the SUS of the I-PEN and the tarsal conjunctiva, even if extremely slight, may induce transient lacrimation, resulting in a decrease in tear osmolarity.…”
Section: Discussionmentioning
confidence: 99%